2017
DOI: 10.1002/jcb.26128
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin Inhibited Migration and Invasion of Human Lung Cancer Cells via Suppression of c‐Met‐Mediated Epithelial‐to‐Mesenchymal Transition

Abstract: Epithelial-to-mesenchymal transition (EMT) is a major process to regulate cell migration and invasion. Inhibition of epidermal growth factor receptor (EGFR)-mediated EMT by tyrosine kinase inhibitors (TKIs) is a strategy to prevent lung cancer invasion. However, drug resistance is emerged and accelerated invasion through other signaling bypassing EGFR after TKIs therapy. c-Met signaling pathway is highly activated in EGFR-mutated lung cancer cells. Targeting c-Met signaling pathway may be a strategy to suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600]. Shikonin exerts anti-cancer effects mainly by inducing apoptosis, necroptosis, autophagy, cell cycle arrest, and by inhibiting cell proliferation, growth and metastasis [593,601,602].…”
Section: Shikoninmentioning
confidence: 99%
See 1 more Smart Citation
“…It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600]. Shikonin exerts anti-cancer effects mainly by inducing apoptosis, necroptosis, autophagy, cell cycle arrest, and by inhibiting cell proliferation, growth and metastasis [593,601,602].…”
Section: Shikoninmentioning
confidence: 99%
“…However, autophagy provides a protective role in shikonin-induced apoptosis in human melanoma A375 cells [608]. In addition, shikonin can suppress metastasis by the inhibition of tyrosine kinase c-Met and integrin (ITG) β1 in human NSCLC A549 cells [602,611].…”
Section: Shikoninmentioning
confidence: 99%
“…[4][5][6][7][8] It was reported that the anti-migration and anti-invasion activities of shikonin was through inhibition of c-Met followed by suppression of epithelial-mesenchymal transition (EMT) in lung cancer cells. 9 Shikonin showed to exert anticancer effects on gallbladder cancer (GBC) cells by inducing apoptosis and regulating the cell cycle arrest via the c-Jun N-terminal kinase (JNK) signaling pathway. 10 Preliminary clinical trials indicated the potential of shikonin for translation into application in clinical oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin has been shown to suppress tumor growth by modulating multiple signaling pathways including p21, PI3K, ERK, and p53 (Jeung et al 2016), and overcome cancer drug resistance such as gefitinib-resistance by inhibiting TrxR and activating the EGFR proteasomal degradation pathway (Li et al 2017). Shikonin could also enhance the antitumor effect of gefitinib in EGFR wildtype lung cancer via inhibition of PKM2/stat3/cyclinD1 signaling (Tang et al 2018), and inhibit migration and invasion of lung cancer cells via inhibition of c-Met mediated EMT (Hsieh et al 2017). It has been reported that shikonin could overcome cisplatin resistance, afatinib resistance, and tamoxifen resistance in several cancer types (Li et al 2018;Zhang et al 2017a;Wang et al 2018d).…”
Section: Discussionmentioning
confidence: 99%